COMPENSATION AS A MEDIATING VARIABLE BETWEEN WORK-LIFE BALANCE AND EMPLOYEE LOYALTY ON JOB SATISFACTION OF GENERATION Z IN THE MANUFACTURING INDUSTRY - Melly Fitriani Andriyana; Nur Cahyadi (Assets : Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
Changes in the dynamics of work in the manufacturing industry require companies to be able to maintain employee job satisfaction, especially among Generation Z, who evaluate jobs not only based on salary, but also on work-life balance and employee loyalty to the company. The purpose of this research is to examine how employee loyalty and work-life balance affect job satisfaction, as well as how remuneration functions as a mediating factor. 150 members of Generation Z who worked in Gresik’s industrial sector participated in the research, which used an explanatory quantitative methodology. An online survey was used to gather data, and PLS-SEM using bootstrapping techniques was used to evaluate the results and determine if the relationships between the variables were significant. The findings indicate that although employee loyalty has no discernible direct impact on workplace happiness, work-life balance does. The impact of loyalty and work-life balance on job satisfaction was shown to be mediated by compensation, which also had a substantial effect. This study confirms that compensation is a key factor that strengthens the job satisfaction of Generation Z in the manufacturing industry.